Interkultural Masyarakat Nanjing dan Chongqing pada perayaan Chūn Jié (春节) - Fadlilah, Jasmine Setya Nur; Rachmalia, Zhafira Vani; Sunarti, Sunarti (Fakultas Sastra Universitas Negeri Malang, 2022)
Chūn Jié (春节) or spring festival is one of the important festivals for the people in China. Chinese Spring Festival or Lunar New Year, or Chinese New Year is the most important festival in China. There are lots of traditions, celebrations, and superstitions associated with the festival. Chinese people celebrate the festival with many traditional activities with the hope of a happy and prosperous next year. This festival marks the beginning of the new year in the lunar calendar and thus marks the start of a new life of prosperity. However, there are many regions in China which, as a result, create various traditions in welcoming the Spring Festival. The method used in this paper is a qualitative method using heuristics, with secondary sources. This paper will be focusing on how the people from Nanjing and Chongqing celebrate Chūn Jié (春节) with their respective traditions.